End of OSLER Test Sessions in Parkinson’s Disease do not Correspond to True Sleep Onset: Results from an Exploratory Study - Neutel, Dulce; Peralta, Rita; Pires, Joana; Bentes, Carla; Ferreira, Joaquim J. (Frontiers in Neurology, 2015)
The aim of the present study was to evaluate the correlation between the end of an OSLER test session and a neurophysiological marker of sleep onset in Parkinson’s disease (PD) patients. Single center study was conducted in PD patients with EDS (Epworth Sleepiness Scale (ESS) >9). The OSLER test was conducted with a concomitant electroencephalography, EMG (mentalis), right and left electroculogram and video monitoring. Neurophysiologic (NP) sleep onset was defined according to AASM criteria (2005). Five PD patients with mean ESS of 14 (10 to 16) were included. OSLER test duration was shorter than 40 minutes in all patients (mean duration 20 minutes and 39 seconds ). No patient fulfilled neurophysiological criteria to sleep onset at the time of OSLER test termination. In 13 OSLER sessions that ended before 40 minutes, eight had microsleeps in the last 30 seconds before the end of the test. NP monitoring showed signs of sleepiness in all patients. In PD patients, the early termination of an OSLER test session may not correspond to NP criteria of sleep onset. However, in all PD patients with abnormal OSLER results there were EEG signs of sleepiness, which do not exclude the potential utility of OSLER test to evaluate the risk of falling asleep.